Prediction of ball velocity during standing throw and gain of velocity obtained by cross over step - Laffaye, G.; Debanne, T. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
This study compared handball throwing velocity in two handball groups: an elite player group and a skilled player group. The gain obtained by the 3-step running is 2.24±0.75 m.s-1 and is independent of the expertise. Elite players are taller (13cm, +6.85%) and heavier (17 kg, +18.91%), have better upper-limb strength than skilled ones (+18%). The high-velocity throwing technique is quite similar for a same population but slightly differs between both samples.